Humanista w dobrym kontakcie, czyli o tutoringu akademickim - Wojciechowska, Julita (Człowiek i Społeczeństwo, 2020)
The aim of the article is to present the basic idea of academic tutoring. This method allows for personalized and in-depth use of experience – based and taught teaching tools by developed in modern humanities in academic teaching.